Deterministic single-ion implantation of rare-earth ions for nanometer-resolution color-center generation - Groot-Berning, Karin; Kornher, Thomas; Jacob, Georg; Stopp, Felix; Dawkins, Samuel T.; Kolesov, Roman; Wrachtrup, Joerg; Singer, Kilian; Schmidt-Kaler, Ferdinand (Physical Review Letters, 2019)
Single dopant atoms or dopant-related defect centers in a solid state matrix are of particular importance among the physical systems proposed for quantum computing and communication, due to their potential to realize a scalable architecture compatible with electronic and photonic integrated circuits. Here, using a deterministic source of single laser-cooled Pr+ ions, we present the fabrication of arrays of praseodymium color centers in yttrium-aluminum-garnet substrates. The beam of single Pr+ ions is extracted from a Paul trap and focused down to 30(9) nm. Using a confocal microscope, we determine a conversion yield into active color centers of up to 50% and realize a placement precision of 34 nm.
CRIS-Team Scopus Importer:2023-03-27